A Review on Possibility to Use Ethanol as a Alternative Fuel in Diesel Engine - Mandalia, Hiren V. (Asian Review of Mechanical Engineering, 2015)
Ethanol is an attractive alternative fuel because it is a renewable bio-based resource, thereby providing the potential to reduce particulate emissions in compression–ignition engines. In this review the properties and specifications of ethanol blended with diesel fuel are discussed. Special emphasis is placed on the factors critical to the potential commercial use of these blends. The effect of the fuel on engine performance, durability and emissions is also considered. The formulation of additives to correct certain key properties and maintain blend stability is suggested as a critical factor in ensuring fuel compatibility with engines. However, the addition of ethanol to diesel fuel simultaneously decreases cetane number, high heating value, aromatics fractions and kinematic viscosity of ethanol blended diesel fuels and changes distillation temperatures. Also for maintaining vehicle safety with these blends may entail fuel tank modifications. Further work is required in specifying acceptable fuel characteristics, confirming the long-term effects on engine durability, and ensuring safety in handling and storing ethanol–diesel blends.